UPAYAKEPALASEKOLAH DALAMMENINGKATKAN MUTU KEGIATAN BELAJAR MENGAJAR DI SMA NEGERI 3 KOTA PRABUMULIH - FEBRIYADI; AGUS SUJARWO; SUGITO (UNISAN JURNAL, 2024)
Research methods with data collection techni questhro ugh observation,interviews, and documentation. Respondents in this study were madrasa heads, teachers, and students at SMA Negeri 3 Kota Prabumulih.The results showedthat the headof the madrasa made several efforts to improve the quality of teaching and learning activities at SMA Negeri 3 Kota Prabumulih, including: (1) conducting regular supervision of teachers, (2)providing training and guidance to teachers in developing (3) improves choolfac ilitiesan dinfrastructure activities through various extracurricular activities, (5) form a curriculum development team to compile and develop a curriculum that is relevant to students' needs. Thus, it can be concluded that the efforts of the madrasa head in improving the quality ofteaching and learning activitiesat supervision, training and guidance ,improvemen toffac ilitiesan dinfrastructure, student tinvolvement, and curriculum development. Alloftheseeffor tsaimto improve the quality of education provided at SMA Negeri 3 Kota Prabumulih so as to create students who are competent and with character. Keywords:HeadofSekolah,Quality,TeachingandLearning Activities